NDM-1 producing Acinetobacter baumannii isolated from a patient repatriated to the Czech Republic from Egypt, July 2011 - Hrabák, Jaroslav; Štolbová, Marta; Študentová, Vendula; Fridrichová, M; Chudáčková, Eva; Žemličková, Helena (Euro surveillance, 2012)
We describe the isolation of an NDM-1-producing Acinetobacter baumannii in a Czech patient repatriated in July 2011 from Egypt. The infection spread to another patient on the same ward. Both isolates showed the same resistance pattern and were susceptible only to colistin. They had an identical PFGE pattern and belonged to the same sequence type ST 1. Sequencing of the blaNDM gene identified the NDM-1 variant of the carbapenemase, surrounded by two copies of insertion sequence ISAba125.
Keywords: Pneumonia, Ventilator-Associated; Gene Amplification; Acinetobacter baumannii; Czech Republic; Humans; techniky typizace bakterií; mikrobiální testy citlivosti; Electrophoresis, Gel, Pulsed-Field; cestování; lidé; amplifikace genu; molekulární sekvence - údaje; ventilátorová pneumonie; antibakteriální látky; Travel; Female; beta-laktamová rezistence; infekce bakteriemi rodu Acinetobacter; Egypt; Bacterial Typing Techniques; pulzní gelová elektroforéza; Bacterial Proteins; Polymerase Chain Reaction; Anti-Bacterial Agents; beta-laktamasy; Male; polymerázová řetězová reakce; bakteriální proteiny; beta-Lactam Resistance; Molecular Sequence Data; Česká republika; Microbial Sensitivity Tests; ženské pohlaví; mužské pohlaví; Acinetobacter Infections; beta-Lactamases